2001
DOI: 10.1248/cpb.49.1314
|View full text |Cite
|
Sign up to set email alerts
|

New .MU.-Opioid Receptor Agonists with Piperazine Moiety.

Abstract: Recently, it has been reported that morphine, a representative m-opioid receptor (MOR) agonist, showed an analgesic activity in the periphery in mice.1) Additionally it has been recognized that tolerance to the peripheral analgesia was not developed after the repeated administration of morphine in mice.2) Furthermore, it has been reported that the MORs were increased around the inflammatory tissues in animals and humans.3,4) These reports indicate that the MOR agonists are useful analgesics in the periphery, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…3) Animals The experiment was performed on male Sprague-Dawley rats weighing 110-150 g (Charles River, Japan). The animals were housed under 12-h light-dark cycle (lights on 7 : 00 a.m.), with room temperature maintained 23Ϯ3°C, and humidity at 50Ϯ20%.…”
Section: H]dpnmentioning
confidence: 99%
See 2 more Smart Citations
“…3) Animals The experiment was performed on male Sprague-Dawley rats weighing 110-150 g (Charles River, Japan). The animals were housed under 12-h light-dark cycle (lights on 7 : 00 a.m.), with room temperature maintained 23Ϯ3°C, and humidity at 50Ϯ20%.…”
Section: H]dpnmentioning
confidence: 99%
“…But recently, it has been reported that when loperamide was administered to a burn on a rat as a peripheal percutaneous cream, it was effective and could not easily pass through the BBB so the manifestion of tolerance did not occur. 2) This report indicates that the peripheral MOR agonists are useful analgesics in the peripheral, especially against inflammatory tissues.In our previous paper, 3) we reported that though our final objective was the synthesis of MOR agonists having peripheral analgesic activity, we intended to synthesize the compounds having more potent activities in two in vitro tests mentioned in the above summary as the first step and then we found compound A accomplishing our purpose (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phenylpiperidine structures, such as loperamide ( 1 ) [ 7 , 8 ], N -desmethylloperamide ( 2 ) [ 9 ], diphenoxylate ( 3 ) [ 10 ], and 4 ( Figure 1 ) [ 11 ], are typical representatives of these compounds. Although diphenoxylate and loperamide are MOR agonists and show affinity and selectivity for the cloned μ human opioid receptor, they do not easily pass through the blood–brain barrier (BBB) [ 12 ], therefore, they are currently mainly used as antidiarrheal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Also, 2-(piperazin-1-yl)pyrazines are important units in many molecules possessing biological activity. [4][5][6] The presence of this structural motif in many substances of biological significance have led to many approaches being developed to access this chemotype, many of which have been employed in the preparation of pharmaceutical agents. [5][6][7] Molecular iodine, firstly produced from brine in Japan, has been used in organic synthesis for a long time.…”
mentioning
confidence: 99%